2008
DOI: 10.2353/ajpath.2008.070293
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Features of Hepatic Cyst Epithelium in Autosomal Dominant Polycystic Kidney Disease

Abstract: We evaluated the morphological and functional features of hepatic cyst epithelium in adult autosomal dominant polycystic kidney disease (ADPKD). In six ADPKD patients, we investigated the morphology of cyst epithelium apical surface by scanning electron microscopy and the expression of estrogen receptors (ERs), insulin-like growth factor 1 (IGF1), IGF1 receptors (IGF1-R), growth hormone receptor, the proliferation marker proliferating cell nuclear antigen, and pAKT by immunohistochemistry and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 51 publications
7
82
0
Order By: Relevance
“…21,28 Although IGF-1 has been proposed to be secreted in cystic fluid of ADPKD patients and may increase proliferation of PKD1 cystic cells, there is little information on the role of IGF-1 in cystogenesis in ADPKD. 29,30 In our model, we observed that FR leads to suppression of circulating IGF-1 levels and expression of IGF-1 in the kidney (Supplemental Figure 9) It is possible that FR may prevent ADPKD via suppression of the IGF-1/IGF-1R pathway. However, the precise mechanistic role of IGF-1 in ADPKD and its implications for the effect of FR remain to be studied.…”
Section: Discussionmentioning
confidence: 89%
“…21,28 Although IGF-1 has been proposed to be secreted in cystic fluid of ADPKD patients and may increase proliferation of PKD1 cystic cells, there is little information on the role of IGF-1 in cystogenesis in ADPKD. 29,30 In our model, we observed that FR leads to suppression of circulating IGF-1 levels and expression of IGF-1 in the kidney (Supplemental Figure 9) It is possible that FR may prevent ADPKD via suppression of the IGF-1/IGF-1R pathway. However, the precise mechanistic role of IGF-1 in ADPKD and its implications for the effect of FR remain to be studied.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, this antibody was shown to be suitable for immunohistochemical experiments in paraYn-embedded tissues (Alvaro et al 2008). BrieXy, after deparaYnization endogenous peroxidase activity and nonspeciWc protein binding of the sections were blocked by 10% hydrogen peroxide solution in double-distilled water for 10 min at room temperature (RT) and 10% normal goat serum (Dako, Hamburg, Germany) for 30 min at RT, respectively, before incubation with the primary antibody at 4°C overnight in a humid chamber (Shandon, Frankfurt a.M., Germany).…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
“…However, for each patient, hepatic cysts grow steadily with age, both in number and size. Although both men and women can develop PCLDs, women usually present a stronger phenotype 1 2 4. Several cytokines, such as interleukin (IL)-6 and IL-8, oestrogens and growth factors (ie, vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), epidermal growth factor (EGF), epithelial derived neutrophil activating peptide 78 (ENA78) and growth regulated oncogene α (GROα)) may be secreted by cholangiocytes lining the hepatic cysts and are present in high levels in cystic fluid 4–7.…”
Section: Introductionmentioning
confidence: 99%